Implementation of the process approach in training for writing journal articles in English - Prastawa, Singgih; Sutrisno, Ribut Agung; Kadun, Satria Omega; Wardhani, Vanessa Kusuma (Universitas Muhammadiyah Malang, 2026)
Writing journal is a part of problem occurring for student congregations in GKSI Mojogedang. This study aims to describe the implementation of a process approach in training members of the Indonesian Sangkakala Christian Church (GKSI) to write academic articles in English. The process approach focuses on the stages of writing, including pre-writing, drafting, revising, editing, and publishing. It is estimated that this method can improve the quality of writing and the confidence of participants. This study uses a qualitative approach with a case study design. Data were collected through direct observation during the training process, in-depth interviews with participants and facilitators, and documentation of participants' written work. The results show that the process approach has a positive impact on improving the academic writing skills of church members in English. Participants showed improvement in their understanding of article structure, use of academic language, and ability to revise their work independently. In addition, this approach encourages collaboration, reflection, and active participation of participants in the writing process. The challenges faced include differences in educational backgrounds and limited training time. These findings suggest that the process approach is effective in non-formal contexts such as church communities, with the caveat that strategies must be tailored to the characteristics of the participants.